Genetic Enhancement of Behavioral Itch Responses in Mice Lacking Phosphoinositide 3-Kinase-γ (PI3Kγ). Issue 1 (14th December 2011) - Lee, Bolam; Descalzi, Giannina; Baek, Jinhee; Kim, Jae-Ick; Lee, Hye-Ryeon; Lee, Kyungmin; Kaang, Bong-Kiun; Zhuo, Min
Phosphoinositide 3-kinases (PI3Ks) are important for synaptic plasticity and various brain functions. The only class IB isoform of PI3K, PI3Kγ, has received the most attention due to its unique roles in synaptic plasticity and cognition. However, the potential role of PI3Kγ in sensory transmission, such as pain and itch has not been examined. In this study, we present the evidence for the first time, that genetic deletion of PI3Kγ enhanced scratching behaviours in histamine-dependent and protease-activated receptor 2 (PAR-2)-dependent itch. In contrast, PI3Kγ-deficient mice did not exhibit enhanced scratching in chloroquine-induced itch, suggesting that PI3Kγ selectively contributes to certain types of behavioal itch response. Furthermore, PI3Kγ-deficient mice exhibited normal acute nociceptive responses to thermal and mechanical noxious stimuli. Behavioral licking responses to intraplantar injections of formalin and mechanical allodynia in a chronic inflammatory pain model (CFA) were also not affected by PI3Kγ gene deletion. Our findings indicate that PI3Kγ selectively contributes to behavioral itching induced by histamine and PAR-2 agonist, but not chloroquine agonist.